Annual feeding rate of the millipede Glomeris marginata on holm oak ( Quercus ilex) leaf litter under Mediterranean conditions (Pedobiologia, 2002)
The annual consumption and assimilation rates of Quercus ilex leaf litter by the millipede Glomeris marginata were estimated under Mediterranean conditions simulated in the laboratory. Measurements were made on six occasions throughout the year to take into account seasonal variations in (i) the quality of decomposing leaves, (ii) the physiological state of the animals, and (iii) temperature plus photoperiod. The mean weight-specific consumption rate was 14 g (dry weight) g-1 (live weight) y-1 , which is much higher than published figures for Mediterranean oak leaf litter. The consumption rate was highest in spring (51 mg g-1 d-1 ) and lowest in summer (28 mg g-1 d-1 ), the summer consumption rate being even lower when determined with air-dried leaves (17 mg g-1 d-1 ). Assimilation efficiency averaged 6 % for the year, with a maximum in spring (9 %) and a minimum in winter (1 %). A much higher assimilation efficiency (29 %) was measured with freshly fallen leaves, but a food preference experiment showed that these leaves were generally avoided and that G. marginata preferred more decomposed leaves despite their lower digestibility. It is concluded that these saprophagous macroarthropods – with field biomasses of 7–11 g (live weight) m-2 – produce considerable amounts of faecal pellets in Mediterranean oak forests.

Annual feeding rate of the millipede Glomeris marginata on holm oak ( Quercus ilex) leaf litter under Mediterranean conditions - DAVID, J. F.; Gillon, Dominique (Pedobiologia, 2002)
The annual consumption and assimilation rates of Quercus ilex leaf litter by the millipede Glomeris marginata were estimated under Mediterranean conditions simulated in the laboratory. Measurements were made on six occasions throughout the year to take into account seasonal variations in (i) the quality of decomposing leaves, (ii) the physiological state of the animals, and (iii) temperature plus photoperiod. The mean weight-specific consumption rate was 14 g (dry weight) g-1 (live weight) y-1 , which is much higher than published figures for Mediterranean oak leaf litter. The consumption rate was highest in spring (51 mg g-1 d-1 ) and lowest in summer (28 mg g-1 d-1 ), the summer consumption rate being even lower when determined with air-dried leaves (17 mg g-1 d-1 ). Assimilation efficiency averaged 6 % for the year, with a maximum in spring (9 %) and a minimum in winter (1 %). A much higher assimilation efficiency (29 %) was measured with freshly fallen leaves, but a food preference experiment showed that these leaves were generally avoided and that G. marginata preferred more decomposed leaves despite their lower digestibility. It is concluded that these saprophagous macroarthropods – with field biomasses of 7–11 g (live weight) m-2 – produce considerable amounts of faecal pellets in Mediterranean oak forests.
Keywords: assimilation efficiency; diplopoda; feeding rate; Mediterranean forests; soil macrofauna